(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
It is necessary to find explanations in the images from the past to understand the ways in which the world was represented, and how their creators -or their read- ers- used to see these images. This paper’s objective is to make an approach to Costa Rica postcards edited from 1900 to 1920, trying to show that they can offer a lot of benefits to the knowledge of history, specifically when in the images we can recognize visual discourses later adopted as social imaginaries. There are some publications with the mission of recollecting, postcards, and those are significant, but it is more important to go even further and develop an iconological reading, that can give us examples of the richness of the visual messages.